BADANIA GENETYCZNE DNA NA UŻYTEK PROCESU KARNEGO - Szczepaniec, Maria (Zeszyty Prawnicze, 2016)
DNA GENETIC TESTING IN CRIMINAL PROCEDURE Summary The article discusses the use of DNA genetic testing for the purposes of criminal procedure. It describes the general principles and methods used in DNA-based tests. It also addresses the issue of the value of haemogenetic examination as evidence, and notes the problem of contamination and the method employed for the collection of samples for comparative tests.